Ulnar Neuropathy Caused by a Widespread Synovial Cyst of the Elbow Joint in a Patient with Rheumatoid Arthritis - Scholz, Christoph; Gierthmuehlen, Mortimer; Egger, Karl; Hauschild, Oliver; van Velthoven-Wurster, V. (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2014)
A 53-year-old man with rheumatoid arthritis presented with radiating pain, numbness, and diminished motor strength in the right hand according to the ulnar nerve functions. Magnetic resonance imaging and peripheral nerve ultrasound revealed a widespread cystic lesion descending from the elbow joint along the ulnar nerve over a length of 8 cm. After relapse under a therapeutic attempt with antirheumatic drugs, neurosurgical exploration was done using peripheral nerve ultrasound. A synovial cyst of the elbow was extirpated as a whole with subsequent anterior synovectomy. The postoperative course was uneventful with gradual recovery of function.
Keywords: rheumatoid arthritis; peripheral neuropathy; ulnar nerve; neurosurgical; decompression; peripheral nerve ultrasound